(untitled) (ENTHYMEMA, 2020)
Here we document how college students responded to a canonical book of Korean poems, Kim Sowol’s 1925 Jindallaekkot (Azaleas), presented in a variety of formats: as part of a 2014 printed facsimile, a 2007 printed scholarly edition, a reading text articulated as a web page on a tablet, and a radical refiguration as a virtual reality forest. We asked students to describe if they enjoyed and felt inspired by their encounters with Kim Sowol’s poetry in these different formats. We also asked if they felt their experiences were educational and if they engendered a desire to share Kim Sowol’s poetry with international peers. Student responses suggest that encounters with novel forms of canonical texts are enjoyable, inspiring, and created a desire to share them with international peers, especially if novel presentations are complemented by more familiar textual idioms, which students found the most educational.